KINERJA KEUANGAN PEMERINTAH DKI JAKARTA DAN JAWA BARAT: DAMPAK PANDEMI COVID19 - Desri yanto; Kusumawardani, Media (Jurnal Riset Terapan Akuntansi, 2024)
The aim of this research is to determine the financial performance of the DKI Jakarta and West Java regional governments before the pandemic, during and after Covid-19 in the time period 2018 to 2022. This research is a quantitative descriptive study by analyzing regional financial performance based on regional financial reports produced by the DKI Jakarta regional government and West Java. The research results show that the financial ratios of the DKI Jakarta regional government are very good in the Regional Financial Independence Ratio, Degree of Decentralization, Regional Tax Effectiveness Ratio and Regional Financial Dependency Ratio. For the West Java regional government, the financial ratios are good. This can be seen in the Ratio of Operational Expenditures to Total Expenditures, Regional Financial Independence Ratio, Degree of Decentralization, Regional Tax Effectiveness Ratio, Ratio, but the Regional Financial Dependency ratio is at a High ratio indicator.Keywords: Regional Government, Covid19, Financial Performance